1996
DOI: 10.1115/1.2824030
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of Interface Bonding Via Substrate Remelting of an Impinging Molten Metal Droplet

Abstract: A molten metal droplet landing and bonding to a solid substrate is investigated with combined analytical, numerical, and experimental techniques. This research supports a novel, thermal spray shape deposition process, referred to as microcasting, capable of rapidly manufacturing near netshape, steel objects. Metallurgical bonding between the impacting droplet and the previous deposition layer improves the strength and material property continuity between the layers, producing high-quality metal objects. A thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The duration of these two phases is much shorter than that necessary for the droplet to solidify and, thus, the initial spreading phase can be neglected (Amon et al, 1996). This assumption decouples the problem from the fluid dynamics and permits it to be simplified to a thermo-mechanical problem.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…The duration of these two phases is much shorter than that necessary for the droplet to solidify and, thus, the initial spreading phase can be neglected (Amon et al, 1996). This assumption decouples the problem from the fluid dynamics and permits it to be simplified to a thermo-mechanical problem.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…They found that h sharply increases to at the upper surface exceeds the solidus temperature may a maximum, then rapidly decreases, and finally reaches a be fully liquid instead of mushy, since a pure metal or a relatively steady state. Amon et al [55] also calculated h dureutectic alloy solidifies at a single temperature.…”
Section: Influence Of the Liquid Fraction Within Incomingmentioning
confidence: 97%
“…Near net shape parts are fabricated by sequentially depositing molten droplets layer by layer [2]. Up to now, the generation of molten metal droplets has been developed into two main modes: continuous jetting [3][4][5][6][7][8] and dropon-demand (DOD) jetting [9,10]. The former mode can produce high-frequency droplets with a piezoelectric ceramic actuator.…”
Section: Introductionmentioning
confidence: 99%